ICT integration in language classroom for sustainable education - Herawati, Herawati; Riyanti, Dwi; Novita, Dewi (Institute of Computer Science (IOCS), 2025)
This study explores the integration of technology in English as a Foreign Language (EFL) classroom, focusing on its application, benefits, and challenges in the context of sustainable education. In the era of Industry 4.0, technology plays a crucial role in enhancing teaching strategies and language learning outcomes. Using a scoping review methodology, this research analyses recent literature to identify trends and theoretical perspectives on the use of Information and Communication Technology (ICT) in EFL instruction. The review reveals that technology integration—such as language learning apps, online platforms, and multimedia tools—can significantly enhance student engagement, motivation, and language proficiency. However, it also identifies key challenges, including limited teacher training, unequal access to digital resources, and resistance to pedagogical change. The study concludes that while technology offers substantial benefits for EFL learning, its effective implementation requires institutional support, teacher readiness, and equitable access to digital tools to ensure sustainable educational outcomes.